Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1371/journal.pgen.1001152
|View full text |Cite
|
Sign up to set email alerts
|

H3K27me3 Profiling of the Endosperm Implies Exclusion of Polycomb Group Protein Targeting by DNA Methylation

Abstract: Polycomb group (PcG) proteins act as evolutionary conserved epigenetic mediators of cell identity because they repress transcriptional programs that are not required at particular developmental stages. Each tissue is likely to have a specific epigenetic profile, which acts as a blueprint for its developmental fate. A hallmark for Polycomb Repressive Complex 2 (PRC2) activity is trimethylated lysine 27 on histone H3 (H3K27me3). In plants, there are distinct PRC2 complexes for vegetative and reproductive develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
173
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(191 citation statements)
references
References 53 publications
(109 reference statements)
18
173
0
Order By: Relevance
“…This may also be the case in E. festucae, where deletion of the H3K27 MTase ΔezhB does not rescue the growth defects of the H3K9 MTase-deficient mutant ΔclrD (22). In plants and animals, cross-talk between different heterochromatin components and the Pc system has been linked to cell type-specific changes in chromatin architecture, raising the possibility that different heterochromatin-based mechanisms could regulate H3K27me3 in different cells even within the same organism (71,81,82).…”
Section: H2amentioning
confidence: 99%
“…This may also be the case in E. festucae, where deletion of the H3K27 MTase ΔezhB does not rescue the growth defects of the H3K9 MTase-deficient mutant ΔclrD (22). In plants and animals, cross-talk between different heterochromatin components and the Pc system has been linked to cell type-specific changes in chromatin architecture, raising the possibility that different heterochromatin-based mechanisms could regulate H3K27me3 in different cells even within the same organism (71,81,82).…”
Section: H2amentioning
confidence: 99%
“…The loss-of-function mutants of IBM1 showed ectopic CHG methylation and H3K9me2 in thousands of genes (Miura et al, 2009a;Inagaki et al, 2010). Recent studies discovered that endosperm H3K27me3 profile identified some transposable elements and protein coding genes that contained a lower level of DNA methylation and were subjected to H3K27me3, whereas these sequences contain dense DNA methylation and are absent of H3K27me3 in vegetative tissues, suggesting that DNA methylation prevents the establishment of H3K27me3 at targets in vegetative tissues (Weinhofer et al, 2010).…”
Section: Prc2 (Fie1)-mediated H3k27me3 Repression Of Gene Expression mentioning
confidence: 99%
“…This and another study concluded that PRC2 can regulate maternal and paternal alleles of MEGs and maternal alleles of PEGs [5] [6]. In endosperm, paternal alleles of PEGs might be protected from PRC2 repression because of DNA methylation continuously present at those loci [25].…”
Section: Polycomb Groupmentioning
confidence: 83%
“…Reduced DNA methylation levels in the endosperm might enable targeting of Polycomb group proteins to selected loci, catalyzing trimethylation of lysine 27 on histone H3 (H3K27me3), a hallmark of silent chromatin [25]. Figure 2C).…”
Section: Polycomb Groupmentioning
confidence: 99%